Deep River promise - Ashenden, Jackie (Ashenden, Jackie. Alaska homecoming., 2021)
Astrid James didn't ask to be mayor of Deep River, but when an arrogant outsider shows up and tries taking charge, she'll have to decide what she's willing to risk.